Playing Rugby With The Truth - Harper, Eric; Ntsime, Patrick (PINS-Psychology in Society, 2026)
This paper attempts to think about the Truth and Reconciliation Commission (TRC) in a different way, by examining a particular event that happened in South Africa while the TRC was in process, namely, the court battle between President Mandela and the South African Rugby and Football Union (SARFU) over racism. This exploration flows into an argument about a political struggle the TRC was caught up in, over who would construct memory. To illustrate this struggle, selected media portrayals of the TRC are compared with ways in which the TRC portrayed itself. Important to these considerations was an examination of the cost (to survivors) of notions of "reconciliation", "truth" and "healing", especially when reparations are not paid. Finally, the paper uses various psychoanalytic lenses to explore the TRC process as a way of seeing the construction of so called white and black psyche.